Chronic consumption of a hypercaloric diet increases neuroinflammation and brain senescence, promoting cognitive decline in middle-aged female Wistar rats - Salas-Venegas, Verónica; Santín-Márquez, Roberto; Ramírez-Carreto, Ricardo Jair; Rodríguez-Cortés, Yesica María; Cano-Martínez, Agustina; Luna-López, Armando; Chavarría, Anahí; Konigsberg, Mina; López-Díazguerrero, Norma Edith (Frontiers in Aging Neuroscience, 2023)
Being overweight and obesity are world health problems, with a higher prevalence in women, defined as abnormal or excessive fat accumulation that increases the risk of chronic diseases. Excess energy leads to adipose expansion, generating hypertrophic adipocytes that produce various pro-inflammatory molecules. These molecules cause chronic low-intensity inflammation, affecting the organism’s functioning and the central nervous system (CNS), inducing neuroinflammation. The neuroinflammatory response during obesity occurs in different structures of the CNS involved in memory and learning, such as the cortex and the hippocampus. Here we analyzed how obesity-related peripheral inflammation can affect CNS physiology, generating neuroinflammation and promoting cellular senescence establishment. Since some studies have shown an increase in senescent cells during aging, obesity, and neurodegenerative diseases, we proposed that cellular senescence participation may contribute to the cognitive decline in an obesity model of middle-aged female Wistar rats. The inflammatory state of 6 and 13 months-old female Wistar rats fed with a hypercaloric diet was measured in serum and CNS (cortex and hippocampus). Memory was evaluated using the novel object recognition (NOR) test; the presence of senescent markers was also determined. Our data suggest that the systemic inflammation generated by obesity induces a neuroinflammatory state in regions involved in learning and memory, with an increase in senescent markers, thus proposing senescence as a potential participant in the negative consequences of obesity in cognition.